Mutation in the leucine-rich repeat C-flanking region of platelet glycoprotein Ibβ impairs assembly of von Willebrand factor receptor - Tang, Jingrong; Stern-Nezer, Sara; Liu, Po-Ching; Matyakhina, Ludmila; Riordan, Michael; Luban, Naomi L. C.; Steinbach, Peter J.; Kaler, Stephen G. (Thrombosis and Haemostasis, 2004)
We describe a syndrome of thrombocytopenia, bleeding episodes, congenital heart disease and facial dysmorphism in a newborn infant, and trace the cause to mutations on chromosome 22 that involve the gene for platelet glycoprotein Ibβ (GPIbβ, Human Genome Organisation gene symbol GPIBB), a critical component of the von Willebrand factor (vWF) receptor. Fluorescence in situ hybridization in transformed lymphoblasts revealed hemizygous microdeletion of 22q11.2 containing the GP1BB locus. DNA sequencing revealed a C to T transition in the patient’s remaining GP1BB allele, predicting a novel proline to serine substitution (Pro96Ser) in the carboxyterminal flanking domain of a leucine-rich repeat. We characterized the mutant GP1BB allele by expression in a cell line (CHOαIX) that stably expresses two other components of the vWF receptor, GPIbα and GPIX. Flow cytometry and confocal imaging of transfected CHOαIX cells demonstrated that P96S GPIbβ abrogates surface assembly of the complex, consistent with platelet flow cytometry studies in the patient. Based on sequence homology to the known crystal structures of two other leucine-rich repeat proteins, the human Nogo receptor and GPIbα, we propose a new structural model of GPIbβ. The model refutes earlier assumptions about cysteine-cysteine interactions in the amino-terminal region of GPIbβ, and predicts a hydrophobic patch the burial of which may contribute to proper conformation of the fully assembled vWF receptor complex.
Keywords: Genetic diseases; platelets; structural biology